A Comparative Study of Anxiety, Depression and Stress during Pregnancy in Working and Non-Working Women - Pal Rubika Rudra, Jha Dr. Dheeraj, Pandey Dr. Vandana, (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The present study investigated difference between anxiety, depression, and stress in working and non-working during pregnancy.50 Working women and 50 non-working total 100 pregnant women were selected by purposive and convenient sampling from different clinics of gynaecologist in Kolkata city (West Bengal) with her/him and subject’s consent.To collect the data Depression Anxiety Stress Scale (DASS-42) developed by Lovibond and Lovibond (1995), to measure the negative emotional states of depression, anxiety and stress was administrated on sample of the study. Data were analysed by Statistical Mean (M), standard deviation (S.D.) and critical ratio or t-test for large sample. According to results we can conclude that There is a significant difference between Depression, Anxiety and Stress in Pregnancy phase of working and non-working women. Research found Mild level of depression, moderate level of anxiety and moderate level of stress in working and non-working women during pregnancy phase.